Inactivation of AMMECR1 is associated with growth, bone, and heart alterations. Issue 2 (14th December 2017) - Moysés‐Oliveira, Mariana; Giannuzzi, Giuliana; Fish, Richard J.; Rosenfeld, Jill A.; Petit, Florence; Soares, Maria de Fatima; Kulikowski, Leslie Domenici; Di‐Battista, Adriana; Zamariolli, Malú; Xia, Fan; Liehr, Thomas; Kosyakova, Nadezda; et al.
Abstract: We report five individuals with loss‐of‐function of the X‐linked AMMECR1 : a girl with a balanced X‐autosome translocation and inactivation of the normal X‐chromosome; two boys with maternally inherited and de novo nonsense variants; and two half‐brothers with maternally inherited microdeletion variants. They present with short stature, cardiac and skeletal abnormalities, and hearing loss. Variants of unknown significance in AMMECR1 in four male patients from two families with partially overlapping phenotypes were previously reported. AMMECR1 is coexpressed with genes implicated in cell cycle regulation, five of which were previously associated with growth and bone alterations. Our knockdown of the zebrafish orthologous gene resulted in phenotypes reminiscent of patients' features. The increased transcript and encoded protein levels of AMMECR1L, an AMMECR1 paralog, in the t(X;9) patient's cells indicate a possible partial compensatory mechanism. AMMECR1 and AMMECR1L proteins dimerize and localize to the nucleus as suggested by their nucleic acid‐binding RAGNYA folds. Our results suggest that AMMECR1 is potentially involved in cell cycle control and linked to a new syndrome with growth, bone, heart, and kidney alterations with or without elliptocytosis. Abstract : We report five individuals with loss‐of‐function of the X‐linked AMMECR1 and short stature, cardiac and skeletal abnormalities and hearing loss. AMMECR1 is co‐expressed with genes implicated in cell cycle regulation, five of which were previously associated with growth and bone alterations. Our knockdown of the zebrafish orthologous gene resulted in phenotypes reminiscent of patients' features. Our results suggest that AMMECR1 is potentially involved in cell cycle control and linked to a new syndrome.